Quantitative fractography by digital image processing: NIH Image macro tools for stereo pair analysis and 3-D reconstruction - Hein, LRO (Blackwell Science, 2001)
A set of NIH Image macro programs was developed to make qualitative and quantitative analyses from digital stereo pictures produced by scanning electron microscopes. These tools were designed for image alignment, anaglyph representation, animation, reconstruction of true elevation surfaces, reconstruction of elevation profiles, true-scale elevation mapping and, for the quantitative approach, surface area and roughness calculations. Limitations on time processing, scanning techniques and programming concepts are also discussed.
Keywords: 3-D reconstruction; image processing; fracture analysis; NIH Image macros; parallax; quantitative fractography; quantitative image analysis; stereo pair analysis; surface roughness